2021
DOI: 10.1177/0081246320985259
|View full text |Cite
|
Sign up to set email alerts
|

Botho as an essential ingredient of African psychology: an insider perspective

Abstract: The African notion of botho appears to have attracted a lot of attention and research efforts in various fields of study. It is presented as a positive concept that is associated with the good side of human beings. In this article, we have adopted an Afrocentric position to analyse the philosophical construct of ‘botho’ as lived and practised in communities that we grew up in. We acknowledge our historical and cultural locatedness in these communities and recognise that this positionality has influenced the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…In their research with LGBTQ+ youth, Bates et al (2020) found that social media served as a ‘safe space’ where individuals find security in community (to connect with others whose identities align with their sense of self), while also expressing narratives of individuality and autonomy. This task of balancing interpersonal relatedness and personal autonomy can be especially intricate in the South African context where emerging adults’ identity development is interwoven with interconnectedness, spirituality, and family roles and responsibilities (Du Plessis et al, 2020; Naudé & Piotrowski, 2022; Sodi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their research with LGBTQ+ youth, Bates et al (2020) found that social media served as a ‘safe space’ where individuals find security in community (to connect with others whose identities align with their sense of self), while also expressing narratives of individuality and autonomy. This task of balancing interpersonal relatedness and personal autonomy can be especially intricate in the South African context where emerging adults’ identity development is interwoven with interconnectedness, spirituality, and family roles and responsibilities (Du Plessis et al, 2020; Naudé & Piotrowski, 2022; Sodi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The narrative journeys of South African emerging adults are thus shaped in a society filled with social complexity, multicultural diversity, continuous transition, sociopolitical concerns, resource constraints, and an unstable economic climate (Alberts & Durrheim, 2018; Du Plessis et al, 2020; Naudé, 2022; Van Lill & Bakker, 2020). South African emerging adults’ identity development is also interwoven with strong ties to African personhood, interconnectedness, spirituality, and family roles and responsibilities (Du Plessis et al, 2020; Naudé & Piotrowski, 2022; Sodi et al, 2021).…”
Section: The Interplay Between Social Media and Identitymentioning
confidence: 99%
“…As trauma is understood as a problem that affects the whole person and the whole community [ 130 ], healing also has communal aspects, with participants describing turning to collective prayer as a powerful source of solace and healing. This relates to the value of ubuntu/botho [ 87 , 88 ] in promoting shared resilience and hope.…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued for the inclusion of a spiritual dimension [ 84 ] and indigenous belief systems [ 63 ] in mental health treatment. Others have pointed towards ubuntu or botho as an important African philosophy to be considered in mental health practice [ 87 , 88 ], as these encompass the spirituality, interconnectedness, and mutual caring that shape African psychology [ 88 ]. An ubuntu/botho framework of psychotherapy emphasizes the diversity of human experiences in pluralistic cultures and embraces a holistic, multidisciplinary approach to healing which holds space for both African and Western treatment perspectives [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first unrotated factor identified was instead one of “Temperance,” contrasting being religious with alcohol use (Thalmayer, Job et al, 2020). Later work among Khoekhoegowab-speakers on the topic of mental health helped to elucidate this distinction as contrasting two key means of coping with adversity and hardship, both involving the value of connecting oneself to a community, for example, the concept of Khoesis (or in nearby languages, Ubuntu or Botho ; Sodi et al, 2021). Do you turn to prayer and community through religion, or do you turn to drink and community at the bar?…”
Section: The Next 50 Years: How To Best Build On This Foundation?mentioning
confidence: 99%